On the position of onomatopoeia in adult language. Evidence from Slovak - Gregová, Renáta (Lingua Posnaniensis, 2022)
onomatopoeic expressions are usually deﬁned as verbal imitations of the sounds from the extra-linguistic reality. the position of onomatopoeia in languages varies cross-linguistically. In standard Slovak, onomatopoeia represents a sub-category of interjections. onomatopoeic words are considered an important part of child’s vocabulary due to their sound-imitative nature and simple structure, but their role in language of the adults is not clear. the study presents the results of the research aimed at the analysis of the place of onomatopoeia in language of adult native Slovak language speakers. the research was carried out on the basis of two questionnaires in which the respondents were asked to (1) identify the sound imitated by the given onomatopoeia, that is, to identify the meaning of the onomatopoeia and (2) to capture the sound they heard by an existing lexicalized onomatopoeia. the research results indicate that although standard Slovak is a language relatively rich in lexicalized onomatopoeic expressions, adult natives are not very familiar with their meaning. Most of the respondents could not identify the sound mimicked by the given onomatopoeia and were not able to capture the sound by the existing lexicalized sound-imitating word. this ﬁnding supports the views about the marginal position of onomatopoeia in adult language.